(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Hasibuan IM, Amelia R, Bimantara Y, Susetya IE, Susilowati A, Basyuni M. 2021. Vegetation and macrozoobenthos diversity in the Percut Sei Tuan mangrove forest, North Sumatra, Indonesia. Biodiversitas 22: 5600-5608. The mangrove forest offers a habitat for a variety of marine species, including macrozoobenthos. Macrozoobenthos live at the bottom of the waters on hard to muddy substrates, where they break down mangrove debris, ensuring microorganisms’ ease in decomposing organic matter into inorganic materials that provide nutrients to producers in the water. The study aimed to determine the vegetation and macrozoobenthos diversity in the Percut Sei Tuan mangrove forest, North Sumatra, Indonesia. This research was executed with vegetation analysis, employing a sampling method in the form of plots, as many as three transects and 66 plots. The sampling of macrozoobenthos was conducted on the substrate surface, roots, and mangrove trunk for three stations and nine plots with a size of 1 m x 1 m. We found 10 true mangrove species where Avicennia marina was the most abundant, found at each seedling, sapling, and tree-stage with an important value index (IVI) of 64.62%, 75.73%, and 92.12%, respectively. Overall, the number of individuals in the species found was 1666.67/Ha at the seedling stage, 1090.91/Ha at the sapling stage, and 842.42/Ha at the tree stage. Seven macrozoobenthos species were found and classified into four classes of Gastropoda, Polychaeta, Mollusca, and Arthropoda, with population abundance values being 9.33 ind/m2 at a station I, 7.44 ind/m2 at station II, and 8.78 ind/m2 at station III. The diversity index (H’) of the observed location was determined to be 1.63-2.06, which was classified into the medium category, while H’ macrozoobenthos ranging from 1.54-1.81 were classified into the low to moderate category. The observed parameters’ physical and chemical factors presented that the condition of the waters in the research area is still considered suitable for supporting macrozoobenthos life, with dissolved oxygen being strongly correlated to macrozoobenthos diversity.